Stationary-phase mutation in the bacterial chromosome: Recombination protein and DNA polymerase IV dependence - Bull, Harold J. (The National Academy of Sciences, 2001)
Several microbial systems have been shown to yield advantageous mutations in slowly growing or nongrowing cultures. In one assay system, the stationary-phase mutation mechanism differs from growth-dependent mutation, demonstrating that the two are different processes. This system assays reversion of a lac frameshift allele on an F′ plasmid in Escherichia coli. The stationary-phase mutation mechanism at lac requires recombination proteins of the RecBCD double-strand-break repair system and the inducible error-prone DNA polymerase IV, and the mutations are mostly −1 deletions in small mononucleotide repeats. This mutation mechanism is proposed to occur by DNA polymerase errors made during replication primed by recombinational double-strand-break repair. It has been suggested that this mechanism is confined to the F plasmid. However, the cells that acquire the adaptive mutations show hypermutation of unrelated chromosomal genes, suggesting that chromosomal sites also might experience recombination protein-dependent stationary-phase mutation. Here we test directly whether the stationary-phase mutations in the bacterial chromosome also occur via a recombination protein- and pol IV-dependent mechanism. We describe an assay for chromosomal mutation in cells carrying the F′ lac. We show that the chromosomal mutation is recombination protein- and pol IV-dependent and also is associated with general hypermutation. The data indicate that, at least in these male cells, recombination protein-dependent stationary-phase mutation is a mechanism of general inducible genetic change capable of affecting genes in the bacterial chromosome.